THE IMPACT OF TECHNOLOGICAL ADVANCES ON THE CHARACTER OF STUDENTS IN THE ERA OF GLOBALIZATION - Sania Latihifa; Sidiq Bagas Apri Yansyah; Tazkia Rahmatika; Rahma Dwi Lestari; Harum Suci (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lampung, 2025)
This research aims to determine the impact of technological advances on the character of students in the era of globalization in Indonesia. The method used is a qualitative descriptive method with a literature study approach. The results show that increasingly rapid technological developments have influenced various areas of life, including the world of education. Technology can provide convenience and fast access to information for students. But on the other hand, unwise use of technology can also threaten students' character formation. Therefore, efforts are needed from various parties, especially educators, to use technology wisely and instill strong character values in students.